Solution theory of fractional SDEs in complete subcritical regimes - Lucio Galeati; Máté Gerencsér (Forum of Mathematics, Sigma)
We consider stochastic differential equations (SDEs) driven by a fractional Brownian motion with a drift coefficient that is allowed to be arbitrarily close to criticality in a scaling sense. We develop a comprehensive solution theory that includes strong existence, path-by-path uniqueness, existence of a solution flow of diffeomorphisms, Malliavin differentiability and